The Caltech Multi-Vehicle Wireless Testbed - Cremean, L.; Dunbar, W.B.; van Gogh, D.; Hickey, J.; Klavins, E.; Meltzer, J.; Murray, R.M. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
We introduce the Caltech Multi-Vehicle Wireless Testbed (MVWT), a platform for testing decentralized control methodologies for multiple vehicle coordination and formation stabilization. The testbed consists of eight mobile vehicles, an overhead vision system that provides GPS-like state information and wireless Ethernet for communications. Each vehicle rests on omni-directional casters and is powered by two high-performance ducted fans. Thus, a unique feature of our testbed is that the vehicles have second order dynamics, requiring real-time feedback algorithms to stabilize the system while performing cooperative tasks. The testbed will be used by various research groups at Caltech and elsewhere to validate theoretical advances in multi-vehicle coordination and control, networked control systems, real-time networking and high confidence distributed computation.